2004
DOI: 10.1097/01.sap.0000123024.80566.8c
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Superiority of Composite Versus Muscle-Only Free Flaps for Skull Coverage

Abstract: Long-term follow-up of free flaps used for skull coverage in this experience has revealed that serious sequela are more likely after muscle-only free flaps. Over the past 2 decades, 8 muscle and 6 composite free flaps have been used in 12 patients. Debulking was the only secondary procedure necessary in 1 composite flap. However, implant extrusion through 1 muscle flap and chronic ulcerations after minor trauma in 2 other muscle flaps could be directly attributed to the thinness of these flaps. Whether these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…One problem with the use of free flaps in reconstructing tongue is that the volume of the flap decreases over time 2,3,6,13) . It is believed that this decrease is due to fatty degeneration of the muscle-fat flap itself or fusion with adipose tissue 9) .…”
Section: Introductionmentioning
confidence: 99%
“…One problem with the use of free flaps in reconstructing tongue is that the volume of the flap decreases over time 2,3,6,13) . It is believed that this decrease is due to fatty degeneration of the muscle-fat flap itself or fusion with adipose tissue 9) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pectoralis major flaps are used most frequently for their feasibility (i.e., easy to elevate) and close location in the operative field. However, muscle flaps are known to atrophy over the postoperative course due to denervation (Hallock, ; Yamaguchi, Kimata, Onoda, Mizukawa, & Onoda, ). Yamaguchi et al () reported that muscle volume decreased to 50% in 12 months and therefore, muscle flaps possibly lose the thickness required to prevent pressure necrosis of the innominate artery.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons in the reconstruction field usually anticipate some postoperative autologous volume loss of the flap [15,16]. There are various factors like muscle atrophy, radiotherapy, and body weight which affect the flap volume to be maintained over the long term [17,18]. MRI is an effective method to evaluate postoperative changes in flap volume (Fig.…”
Section: Discussionmentioning
confidence: 99%